Evaluation of PDIR-Now Satellite Rainfall Data on Observational Rainfall Data (Case Study: Taktakan District, Serang City, Banten) - Lutfiah, Qonita; Purnaditya, Ngakan Putu; Priyambodho, Bambang Adhi; Wigati, Restu; Subekti, Subekti (Jurnal Fondasi, 2024)
Rainfall data is one of the important initial inputs in hydrological analysis, but it is often incomplete due to various constraints such as damage to measuring instruments or uneven distribution of measurement stations. To overcome this problem, weather observation with satellites can be used. However, before using satellite rainfall data, it is necessary to test its suitability with field data to ensure its accuracy. This study aims to evaluate the PDIR-Now satellite rainfall data on observation rainfall data in Serang City to determine the feasibility of using satellite rainfall data and the influence of rain periods (daily (>50mm/day), 15 days, and monthly) on the reliability of satellite data. The analysis method in this study uses statistical analysis in the form of regression analysis at the calibration stage and RMSE, NSE, and Pearson (r) correlation coefficient at the validation stage. Based on the results of the study , it is known that the PDIR-Now satellite can estimate the best rainfall in the monthly period.